"The contemporary, irreverent brand of youth with an independent streak": BAT's youth promotions in Myanmar. Issue 1 (25th February 2004) - Chapman, S
Abstract : "British American Tobacco strongly believes children should not smoke, and smoking should only be for adults who understand the risks associated with it. Our Group companies support and run programmes worldwide tackling underage smoking, and we are committed to pooling our resources and experience globally with others in the tobacco industry—and with governments and NGOs—to help prevent youth smoking. Along with the other two largest international tobacco groups—Philip Morris International and Japan Tobacco International—our Group companies have funded and supported more than 130 Youth Smoking Prevention (YSP) programmes in more than 70 countries. ...We fully support laws and regulations on a minimum age for buying tobacco products, and penalties for retailers who break the law. Our company policy worldwide is not to market to anyone under 18 years old, or more if the law in a particular country sets the age higher."— BAT website November 2003